x(k 2) 2x(k 1) x(k) = u(k),x(0)=0,x(1)=0,u(k)=k (k=0,1,2,…),符合描述的选项为()。_
x(k 2) 2x(k 1) x(k) = u(k),x(0)=0,x(1)=0,u(k)=k (k=0,1,2,…),符合描述的选项为()。_
公式变形:(1)已知U=(U≠0),求k;(2)已知U=(U≠0),求t.
公式变形:(1)已知U=(U≠0),求k;(2)已知U=(U≠0),求t.
f(k)=k(k—1)u(k—1)
f(k)=k(k—1)u(k—1)
设(X,Y)的分布律为[img=317x47]1803c4763fc5f8e.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]1803c4763fc5f8e.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]17de6694cf27b19.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]17de6694cf27b19.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]180306cf74acc90.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]180306cf74acc90.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]1803a655b691efe.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]1803a655b691efe.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]1803a2cb5c8d407.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]1803a2cb5c8d407.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]1803a0ae2ea89a8.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=317x47]1803a0ae2ea89a8.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=242x36]17e43948588a464.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7
设(X,Y)的分布律为[img=242x36]17e43948588a464.png[/img]U=XY, 则P(U=1)等于 A: 4/7 B: 3/7 C: 2/7 D: 1/7